TRANSFORMING PHILIPPINES EVENTS: STRATEGIC PLANNING, MARKETING, AND SUSTAINABILITY FOR DYNAMIC MICE AND BEYOND (2019-2023) - Galapate, Wendell L; Inducil, Joemar; Animas, Melbert (International Journal of Sustainable Competitiveness on Tourism, 2024)
In an ever-evolving landscape of worldwide company as well as tourism, the Conferences, Motivations, Conferences, as well as Exhibitions (MICE) sector has become an essential chauffeur of financial growth, expertise exchange, and also cultural enrichment. This term paper explores the transformative trip taken on by the Philippines' events market from 2019 to 2023, concentrating on the tactical planning, marketing strategies, as well as sustainability efforts that have formed its trajectory. The Philippines, renowned for its natural elegance as well as warm friendliness, provides a fascinating background for MICE activities, which have actually progressively come to be critical in harnessing the country's potential on the international phase. This study utilizes a thorough strategy, combining qualitative as well as measurable study methods. Our objective is to not only give an alternative summary however also to uncover nuances that inform the methods reviewed. By outlining our research procedures, from data collection to analysis, we enhance the paper's trustworthiness and also transparency. Taking into account the above, this research paper finishes in a clear thesis statement that envelops its core focus and purpose: to shed light on the transformative journey of the Philippines' occasions market, highlighting its calculated evolution, marketing characteristics, and sustainability efforts within the world of MICE activities. Subsequently, the paper concludes this introduction with a rundown that sneak peeks the future areas, serving as a roadmap for viewers as they navigate through the details of the Philippines' trip in redefining its events landscape.